Preparation of Cu2Sn3S7 Thin-Film Using a Three-Step Bake-Sulfurization-Sintering Process and Film Characterization. (11th October 2015) - Lui, Tai-Hsiang; Hung, Fei-Yi; Lui, Truan-Sheng; Chen, Kuan-Jen
Abstract : Cu2 Sn3 S7 (CTS) can be used as the light absorbing layer for thin-film solar cells due to its good optical properties. In this research, the powder, baking, sulfur, and sintering (PBSS) process was used instead of vacuum sputtering or electrochemical preparation to form CTS. During sintering, Cu and Sn powders mixed in stoichiometric ratio were coated to form the thin-film precursor. It was sulfurized in a sulfur atmosphere to form CTS. The CTS film metallurgy mechanism was investigated. After sintering at 500°C, the thin film formed the Cu2 Sn3 S7 phase and no impurity phase, improving its energy band gap. The interface of CTS film is continuous and the formation of intermetallic compound layer can increase the carrier concentration and mobility. Therefore, PBSS process prepared CTS can potentially be used as a solar cell absorption layer.